Teacher Performance of Cikeas Nature School: An Analysis of Learning Agility and Work Culture During Work From Home - Hartono, Bambang Dwi; Fadilah, Hupron; Akbar, Firman Muhammad Abdurrohman (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2023)
The pandemic caused by Covid-19 in early 2020 has transformed the learning process in schools. The rapid changes in students' learning ways require teachers to have the ability and willingness to learn new things quickly and adapt them directly in today's challenging situations. The purpose of this research is to analyze the effect of learning agility and work culture during work-from-home (WFH) on teacher performance at Sekolah Alam Cikeas. This type of research is a quantitative research that uses regression analysis technique by collecting data through online survey methods with respondents from all teachers of Sekolah Alam Cikeas, Bogor from the Playgroup, Kindergarten, Elementary, Middle and High School levels with 56 respondents, The results of the study support all the hypotheses that have been proposed. Learning Agility (X1) has significant intervention on Teachers Performance (Y) with (result) bigger than critic score (6,974 > 2,005), Working Environment (X2) has significant intervention on Teachers Performance (Y) with (result) bigger than critic score (2,208 > 2,005). The result of R2 from X1 and X2 to Y with a score of coefficient determinate (R2) 0.699 or 69.9 in percentage. It means that X1 and X2 give intervention on Y about 69.9%. The rest of it (30.1%) is influenced by other factors.